A Case Study on Code Mixing of “Debate Capres & Cawapres 2024’” in Presidential Election - Destri Yani Puspita Sari Gultom; Hutauruk, Bertaria Sohnata; Sinaga, Yanti Kristina (Innovative: Journal Of Social Science Research, 2024)
This research discusses about type and factors of code-mixing. The purpose of this thesis to analyze the type of code-mixing that used in Debate ‘’Capres & Cawapres 2024’’ In Presidential Election, the code-mixing’s utterances into three types : Code mixing of Intra-sentential, Code mixing of Lexical-sentential and Change pronounciation, It also analyzes the factors/reason that motivated the candidate uttarances in two languages, Indonesia and English. This research used qualitative method to analyze the types and factors of code-mixing. The procedures of this research are: the data (the students’ conversation which arranged by two languages are classified into three types of code-mixing based on Hoffman (1991) theory. Then, the data analyze about the factors which motivated the candidate to code-mix their conversation in debate Capres & Cawapres 2024 In Presidential Election based on Hoffman (1991) theory. The result of this research, firstly the types of code-mixing, there were Code mixing of intra sentential from 38 words, Code mixing intra lexical 9 words and Change of pronounciaton 3 words. and the factors of Code mixing in Debate Capres & Cawapres 2024 In Presidential Election includes Talking particular topic 26 words. Secondly, the factors of code-mixing, there was The factors of Code mixing in Debate Capres & Cawapres 2024 In Presidential Election includes Talking particular topic 26 words (52%), Repetition used for clariffication 9 words (18%), Intention of clarifying the speech content for interlocutor 12 words (24%) and Interjection 3 words (6%).